Measuring God Mysticism: New Results of the Short Version of the God Mysticism Scale - Caycho-Rodríguez, Tomás (Pastoral psychology, 2023)
The brief God Mysticism Scale (GMS-B) is a 12-item scale that assesses the perception of God mysticism. The study aimed to evaluate the psychometric properties of the Spanish version of the GMS-B. The sample consisted of 421 young Peruvians from the city of Lima with a mean age of 26.76 years, recruited by convenience sampling using a snowball method. Construct validity, internal consistency reliability, difficulty and discrimination indices of the items, and measurement invariance across sex of the GMS-B were evaluated using procedures derived from classical test theory and item response theory. A confirmatory factor analysis suggested that the original model of two correlated factors did not show adequate fit indices. For this reason, after testing a set of factorial models, it was determined that a brief model of five items written in a positive manner (GMS-5) presented the best fit. In addition, the GMS-5 presented adequate reliability indices (α = 0.94; ω = 0.94), all the items presented adequate discrimination indices, and the difficulty parameters increased monotonically. Therefore, a higher level of the perception of God mysticism is necessary to answer the higher answer options on the scale (for example, respond to option 9 = Definitely true from my experience). Finally, the GMS-5 showed evidence of being strictly invariant for the groups of men and women. In conclusion, the GMS-5 is a unidimensional, reliable, and invariant instrument to assess mysticism among young men and women in Peru.